In vitro investigation of antidiabetic and antiglycation activities of methanolic extract of Ficus deltoidea Jack varieties - Mohd Dom, Nur Sumirah (2021)
Diabetes mellitus has been listed as one of the leading death factors in the world which associated with glucose uptake activity in the human body. Nowadays, the usage of medicinal plants for the management of diabetes mellitus has gained interest even though many antidiabetic drugs are available in the market. This could possibly be due to the limitations of these drugs such as adverse effects and poor clinical efficacy. Therefore, searching for new effective antidiabetic agents should be continued. Ficus deltoidea (F. deltoidea) or also known as Mas Cotek is a local medicinal plant in Malaysia that has been used as a supplement to promote health and traditionally claimed to possess antidiabetic effect. However, the scientific studies to confirm its efficacy and its possible mode of actions are still inadequate. This study was done to authenticate the antidiabetic property of in vitro antihyperglycemic mechanisms evaluation of F. deltoidea varieties, to elucidate the potential of the plant to stimulate insulin secretion from β-pancreatic cells, to enhance glucose uptake by adipocytes and muscle cells, to screen glucose uptake inhibition activity in adipocytes and muscle cells in the presence of LY294002 (PI3-Kinase inhibitor) and ALLN (CAP inhibitor), to assess the insulin sensitizing activity in adipocytes cells and to observe the expression of PPAR-gamma, PI3 Kinase, GLUT4 and CAP gene. The inhibition of advanced glycation end products formation, protein oxidation, total phenolic contents and antioxidative effects of the plant were also monitored. The viability of cells that were used in the in vitro evaluation of antihyperglycemic mechanisms in the presence of F. deltoidea extracts was determined using MTT assay. ii The viability study showed that methanolic extract of F. deltoidea varieties did not possess any cytotoxic effect at concentration of 100 μg/ ml and this concentration was used to measure the antidiabetic mechanism of F. deltoidea varieties extract in BRIN BD11 pancreatic, 3T3FF42A adipocytes and L6 myotubes cells. For insulin secretion study, F. deltoidea variety intermedia stimulated the highest insulin secretion followed by F. deltoidea variety kunstleri and F. deltoidea variety trengganuensis. The result indicated that the insulin secretory action of the extracts involved KATP channel-dependent and KATP channel-independent pathways. F. deltoidea variety trengganuensis, F. deltoidea variety kunstleri and F. deltoidea variety intermedia also significantly enhanced basal and insulin-mediated glucose uptake into adipocytes and muscles cells. The extracts showed either insulin-mimetic or insulin-sensitizing activity or combination of both activities during enhancing glucose uptake into these cells. Meanwhile, the result of glucose uptake inhibition assay of the extracts demonstrated that insulin stimulated glucose uptake followed phosphatidylinositiol-3-kinase-independent (PI3K) mechanism in L6 muscle and 3T3F442A adipocytes cells. In L6 myotubes cells, the highest glucose uptake activity was observed when treated with F. deltoidea variety trengganuensis and F. deltoidea variety intermedia meanwhile in adipocytes, the highest activity was found when treated with F. deltoidea variety trengganuensis. Additionally, in gene expression study, the most upregulation of PPAR-gamma gene was expressed significantly at 24 hours with the highest in F. deltoidea variety kunstleri followed by F. deltoidea variety intermedia and F. deltoidea variety trengganuensis. The novelty of this study is about the investigation of antiglycation properties of F. deltoidea varieties which significantly inhibited the formation of advanced-glycation end-products (AGEs). In conjunction with a reduction of fructosamine level, the plant extracts also increased the thiol groups level and inhibited the formation of protein carbonyl. No previous report published about the potential of F. deltoidea plant to inhibit the formation of AGEs. The highest antiglycation activity was observed in F. deltoidea variety intermedia which also depicted the highest phenolic content and reducing power activities. The correlation study between total phenolic content and antiglycation activity, DPPH radical scavenging activity and reducing power activity showed (-1.0 ≥ r ≤ 1), (-1.0 ≥ r ≤ 1) and (-0.69 ≥ r ≤ 1.0) respectively. In conclusion, this study had shown that F. deltoidea able to reduce hyperglycemia with mechanisms such as stimulation of insulin secretion from pancreatic β-cells, enhancement of glucose uptake into adipocytes and muscle cells and effects of insulin stimulated glucose uptake is through independent type of PI3K pathway. Insulin-sensitizing activities exhibited by F. deltoidea varieties indicated that this plant has the ability to alleviate insulin resistance and may potentially be beneficial for the treatment of type 2 diabetes mellitus with insulin-resistance condition. Finally, the F. deltoidea plant extract also contained phenolic compounds, possessed antioxidant and antiglycation effects that may offer remarkable prospects for the preventive treatment of AGE-mediated diabetic complications. iii Hence, F. deltoidea varieties may offer good therapeutic potential to reduce the complications of diabetes mellitus.